2012
DOI: 10.1017/s0007114512000165
|View full text |Cite
|
Sign up to set email alerts
|

Sweet buttermilk intake reduces colonisation and translocation ofListeria monocytogenesin rats by inhibiting mucosal pathogen adherence

Abstract: The bovine milk fat globule membrane (MFGM) contains several antimicrobial components with proven efficacyin vitro, butin vivoevidence is scarce. The present study was performed to determine the efficacy of the bovine MFGMin vivo.Rats were fed diets based on bovine skimmed milk powder (low in MFGM) or bovine sweet buttermilk powder (high in MFGM). After dietary adaptation, rats were orally infected withSalmone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
29
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 33 publications
(47 reference statements)
0
29
0
2
Order By: Relevance
“…Sweet buttermilk powder contains milk fat globule membrane (MFGM) which prevents adherence of pathogen to intestinal mucosa and protects against listeriosis infection (Sprong et al 2012). Bacteriocins, disinfectants, phages, proper processing and packaging practices in food processing industries can limit spread of Listeria to human population through the food chain.…”
Section: Prevention and Controlmentioning
confidence: 99%
“…Sweet buttermilk powder contains milk fat globule membrane (MFGM) which prevents adherence of pathogen to intestinal mucosa and protects against listeriosis infection (Sprong et al 2012). Bacteriocins, disinfectants, phages, proper processing and packaging practices in food processing industries can limit spread of Listeria to human population through the food chain.…”
Section: Prevention and Controlmentioning
confidence: 99%
“…Furthermore, a HMO pool has been shown to reduce EPEC colonisation in mice (Manthey et al, 2014). Interestingly, a bovine MFGM fraction has been shown to reduce Listeria monocytogenes colonisation in a rat model (Sprong, Hulstein, Lambers, & van der Meer, 2012) and H. pylori colonisation in a mouse model (Wang et al, 2001). Although these studies indicate the anti-infective activity of the dMFGM fraction against EHEC could also be viable in vivo, further studies are required to validate this.…”
Section: Dmfgm Reduced the Association Of E Coli O157:h7 With Ht-29 mentioning
confidence: 99%
“…Interestingly, a study examining the incidence of acute otitis media (AOM) and antipyretic use in human infants found that MFGM supplementation in formula resulted in decreased AOM and fewer days with fever compared to infants consuming control formula24. Additional studies using rodent models (>6 weeks old) have examined the effects of MFGM supplementation on infection and inflammation in vivo and in vitro 252627. Components of MFGM display in vitro bactericidal activity against several foodborne pathogens, including Campylobacter jejuni, Salmonella enteriditis , and Listeria monocytogenes 25.…”
mentioning
confidence: 99%
“…Additional studies using rodent models (>6 weeks old) have examined the effects of MFGM supplementation on infection and inflammation in vivo and in vitro 252627. Components of MFGM display in vitro bactericidal activity against several foodborne pathogens, including Campylobacter jejuni, Salmonella enteriditis , and Listeria monocytogenes 25. In vivo , rats supplemented with MFGM and then infected with L. monocytogenes were protected against pathogen colonization and translocation25.…”
mentioning
confidence: 99%
See 1 more Smart Citation